International Academy of Health Sciences Informatics (IAHSI): Strategy and Focus Areas, 1st Version - Martin-Sanchez, Fernando; Ball, Marion J.; Kimura, Michio; Otero, Paula; Huesing, Elaine; Lehmann, Christoph U.; Haux, Reinhold (Yearbook of Medical Informatics, 2020)
Background: The International Academy of Health Sciences Informatics (IAHSI) is the Academy of the International Medical Informatics Association (IMIA). As an international forum for peers in biomedical and health informatics, the Academy shall play an important role in exchanging knowledge, providing education and training, and producing policy documents.Objectives: A major priority of the Academy’s activities in its inaugural phase was to define its strategy and focus areas in accordance with its objectives and to prioritize the Academy’s work, which can then be transferred to respective taskforces.Method: This document reflects the major outcomes of intensive discussions that occurred during 2019. It was presented at the Academy’s 3rd Plenary on August 25th, 2019, in Lyon, France.Results: Regardless of the ‘living nature’ of the strategy and focus areas document, it was concluded during the Plenary that the first version, which will be used as a base for decisions on the Academy’s future activities, should be made available to a broad audience. Three out of eight ‘Visions for IAHSI‘, presented in the IMIA Yearbook of Medical Informatics 2018, were identified as central for developing, implementing, and evaluating the Academy’s strategic directions: (1) advise governments and organizations on developing health and health sciences through informatics, (2) stimulate progress in biomedical and health informatics research, education, and practice, and (3) share and exchange knowledge. Taskforces shall be implemented to work in the following areas, which were considered as priority themes: (1) artificial intelligence in health: future collaboration of entities with natural and with artificial intelligence in health care, and (2) current landscape of standards for digital health.Conclusions: Taskforces are now being established. Besides specific key performance indicators, suggested for monitoring the work of theses taskforces, the strategy to monitor the progress of the Academy itself has to be measured by relevant and acceptable metrics.
Keywords: Biomedical and health informatics; Medical informatics; Health informatics; Academy of Sciences; International Academy of Health Sciences Informatics